2023
DOI: 10.7150/ijms.84729
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ficolin-3 expression is associated with poor prognosis in patients with hepatocellular carcinoma

Abstract: Background: Ficolin-3 (FCN3) is a well-known circulating pattern recognition molecule which plays a role in host immune responses to cancer via activation of the lectin complement pathway. Nevertheless, the clinical significance of FCN3 in patients with hepatocellular carcinoma (HCC) is unclear. Methods: Eighty-seven HCC patients who received hepatectomy at our hospital were included. Immunohistochemical staining was used to assess the FCN3 expression in both tumorous and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interestingly, ficolin-3, to which MASP-3 is predominantly associated in human serum [41], also may act as a tumor-suppressor agent. It has been shown that the expression of the FCN3 gene is lower in the case of different cancers [250], and a recent study demonstrated that hepatocellular carcinoma patients with a high FCN3 expression had a significantly better overall survival [251]. Although the mechanism is far from clear [252], we can speculate whether MASP-3 may contribute to the tumor suppressor phenomenon in this case.…”
Section: Role In Cancermentioning
confidence: 58%
“…Interestingly, ficolin-3, to which MASP-3 is predominantly associated in human serum [41], also may act as a tumor-suppressor agent. It has been shown that the expression of the FCN3 gene is lower in the case of different cancers [250], and a recent study demonstrated that hepatocellular carcinoma patients with a high FCN3 expression had a significantly better overall survival [251]. Although the mechanism is far from clear [252], we can speculate whether MASP-3 may contribute to the tumor suppressor phenomenon in this case.…”
Section: Role In Cancermentioning
confidence: 58%
“…patients with high FCN3 expression had a higher overall survival rate than those with low FCN3 expression (p = 0.031), which was consistent with our study. And high FCN3 expression in tumor tissue was independently associated with better overall survival (p = 0.042) (Chen et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…GDF11 expression was assessed using both IHC and histochemical scoring (H-score) methods, as described in previous studies [29,30]. Both cytoplasmic and membranous expressions were included and considered positive.…”
Section: Evaluation Of Immunohistochemical Stainingmentioning
confidence: 99%